Automated Solar Powered Street Lighting System with Super Capacitors - Pena, Alvin T Dela; Quezon, Clarissa F; Feliciano, Christian Q (Edelweiss Applied Science and Technology, 2020)
The researchers came up to conduct a study in creating a street lighting system powered up by solar panels that sustains its own power as a standalone system off the grid line. By analyzing the collected data regarding the power consumption of the institution where in every 15% increase in the student’s population, there is 20% increase in the electric bill consumption rate, that is why the researchers continue to expand their previous study, the charging station that gives an alternative source of electrical energy for mobile devices in the institution, to consider a free energy that can be a source of light during night time, this may lessen the power consumption in the near future not only by supplying mobile devices but by also illuminating the environment of the campus. Two hardware designs were constructed and tested as an initial hardware design to control the lighting system namely; a microcontroller unit that will act as the charge controller for the storage unit and a relay module using discrete components that will also act with the same function. The study concluded that the installation of a relay module alone as the charge controller to automatically cut-off the full charge voltage and turn on the charging when voltage in the storage unit is drain enhances the power management capability and storage of the lighting system in comparison to the other design which consumes a greater amount of power in operating the sensor control unit 24/7. The charging unit that uses the super capacitors maximizes the charging time into an average of 136.567 minutes compared to the existing design that has twice of its charging time condition which is equivalent to more than six(6) hours. The researchers recommended that the Colegio de San Juan de Letran, Bataan should implement the installation of this project study, or another study for improving the hardware design components of the system which can be extended to the employees, teachers and students of the institution.